A cohort study comparing the new maternal health care program with the standard program in Qazvin Province, Iran - Jourabchi, Zinat (2012)
Maternal morbidity and mortality continue to exert a severe toll on mothers worldwide and bring into sharp focus the quality of maternal health care especially in developing countries. This cohort study compared the outcome of maternal health care from two programs, one with preconception care, lower number of prenatal care visits, a formalized referral process and postpartum care named integrated maternal health care (IMHC) and the other without these characteristics (Standard program). The main objective of study was aimed at evaluating the impact of these programs on gestational complications and birth outcomes in two cities of Qazvin Province, Iran. Alvand City started the new program or IMHC (with preconception care) in 2007. Of 940 mothers (16-35 years of age) screened at eight maternal care health clinics in each city, 484 were found to be eligible for study. Of these, 450 mothers consented and were followed up from the time of registration at the maternal health care clinic until six weeks after delivery. Of the 450 mothers, 147 (63.4%) had preconception care, all of whom resided in Alvand city. In the IMHC, the number of prenatal care visits were less than in the standard program (a mean of 5 versus 9 visits, p = 0.001). During first and second trimesters, proportionately more referrals of pregnant mothers to specialized care were made in the IMHC (25.5 % in the first trimester and 39.4% in the second trimester for Alvand and 6.8 % and 12.9 % respectively for Qazvin) (p<0.05). Anemia during pregnancy was significantly more in the IMHC for the second and third trimesters (p<0.05). Gestational hypertension was significantly lower in the IMHC during second and third trimesters (p<0.05). Rate of low birth weight «2500gr) was 11.0 % in the standard program versus 6.9 % in the IMHC. Preterm birth « 37 week) was significantly less in the IMHC program and most maternal and neonatal complications were less in the IMHC as well. Neonatal mortality was not significantly different (p<0.05). No maternal mortality reported in any group. In addition, there was a significant association between type of program and the risk of the gestational hypertension. The risk of gestational hypertension in the IMHC was significantly lower than in women in the standard program (adjusted OR=0.164; 95% CI =0.053, 0.506). Moreover, an association was observed between type of program and the risk of the birth outcomes. There was less risk of preterm birth (OR= 0.478; 95% CI= 0.240, 0.952), maternal complication (OR= 0.532; 95% CI=0.344, 0.823) and neonatal complication (OR= 0.503; 95% CI= 0.318, 0.796) in IMHC program. Preconception care had the significant association with gestational hypertension, preterm labor, preterm birth, low birth weight, maternal complication and neonatal complication. The findings of the present study indicated advantages of a new program (IMHC) that associated with lower rate of gestational complication or adverse birth outcomes. Therefore, it is necessary to emphasize benefits of IMHC, including the preconception care, low number of prenatal visits, formulized referral process and postpartum care.